The strength of corticomotoneuronal drive underlies ALS split phenotypes and reflects early upper motor neuron dysfunction - Andrew Eisen; Peter Bede (Brain and Behavior, 2021)
Abstract Background Split phenotypes, (split hand, elbow, leg, and foot), are probably unique to ALS, and are characterized by having a shared peripheral input of both affected and unaffected muscles. This implies an anatomical origin rostral to the spinal cord, primarily within the cerebral cortex. Therefore, split phenotypes are a potential marker of ALS upper motor neuron pathology. However, to date, reports documenting upper motor neuron dysfunction in split phenotypes have been limited to using transcranial magnetic stimulation and cortical threshold tracking techniques. Here, we consider several other potential methodologies that could confirm a primary upper motor neuron pathology in split phenotypes. Methods We review the potential of: 1. measuring the compound excitatory post‐synaptic potential recorded from a single activated motor unit, 2. cortical‐muscular coherence, and 3. new advanced modalities of neuroimaging (high‐resolution imaging protocols, ultra‐high field MRI platforms [7T], and novel Non‐Gaussian diffusion models). Conclusions We propose that muscles involved in split phenotypes are those functionally involved in the human motor repertoire used particularly in complex activities. Their anterior horn cells receive the strongest corticomotoneuronal input. This is also true of the weakest muscles that are the earliest to be affected in ALS. Descriptions of split hand in non‐ALS cases and proposals that peripheral nerve or muscle dysfunction may be causative are contentious. Only a few carefully controlled cases of each form of split phenotype, using upper motor neuron directed methodologies, are necessary to prove our postulate.